Guideline for herbal medicine research - Syed Mohamed, Ami Fazlin; Jamal, Jamia Azdina; Marik Singh, Jaspal Kaur; Narayanan, Damenthi Nair; Zakaria, Zaril Harza; Ramasamy, Seetha; Zainol, Murizal; Muhammad, Hussin; Ismail, Noraisha Akma; Mohd Helan, Mohd Helme; Jaganathan King, Seetha; Jusoh, Samsiah; et al. (National Committee for Research and Development of Herbal Medicine (NRDHM), 2023)
Herbal medicine is widely used in Traditional and Complementary Medicine (T&CM) practices. With its increasing use within the Malaysian community, there needs to be more specific guidance on the requirements for herbal medicine research to produce evidence-based herbal medicine products with therapeutic claims. Therefore, the pathway of herbal product development involving preclinical and clinical research must be well outlined in tandem with the ‘Guideline on Natural Products with Therapeutic Claim’ from the regulators. The primary purpose of this guideline is to provide structured guidance to be utilised by researchers, academicians, clinicians, T&CM practitioners, and relevant stakeholders of the herbal industry. This guideline outlines a concise yet informative description of the prerequisites and processes involved in planning and conducting herbal medicine-related research in the Malaysian context. This guideline will bridge the gap often associated with the population's demand for other treatment options besides conventional medicine. This effort will also help accommodate the growing interest in herbal medicine research and spur the discovery of herbal products with therapeutic claims in Malaysia.